Determinants of Corporate Value in Indonesia: Testing the Interaction Effect of Firm Age - Stevani; Wendy (Ilomata International Journal of Management, 2024)
This study aims to examine the effect of capital structure, profitability, institutional ownership, and company size on corporate value in Indonesia, by considering firm age as a moderation variable. This research focuses on primary consumer sector companies on the Indonesia Stock Exchange (IDX) and obtained 295 panel data observations. Moderated regression analysis is used to estimate the interaction model of firm age on the relationship between independent variables and corporate value. The results showed that capital structure and company size had a positive influence on company value, while profitability and institutional ownership did not have a significant influence. Furthermore, firm age moderates the capital structure, as well as changes the direction of influence of institutional ownership and firm size on firm value. However, firm age does not moderate the influence of profitability on firm value. The implication of this study is the importance of considering other firm value proxies, as well as the need for grouping and testing in different economic conditions to increase the external validity.